The Impact of Maternal Age on the Incidence of Low Birth Weight in Newborns - Chrisye Rani Kuheba; Rifzul Maulina; Anik Sri Purwanti (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
Low birth weight (LBW) is a significant public health problem, with varying prevalence across countries. According to data from the World Health Organization (WHO), approximately 15% of all births worldwide are LBW babies. LBW can be caused by various factors, including maternal health conditions, nutritional status, and environmental factors. One factor that is often overlooked is maternal age during pregnancy. This study aims to explore the relationship between maternal age and the incidence of LBW. Research This study used an observational design with a cross-sectional approach. The sample consisted of 200 pregnant women who gave birth at the Hospital in 2024. Data were collected through medical record data tracing, which included maternal age, infant birth weight, and other risk factors. Statistical analysis was performed using the chi-square test to determine the relationship between maternal age variables and LBW. Results: The results of the analysis showed that 32% of the total babies born had LBW. From the age group under 20 years, the prevalence of LBW reached 15%, while in the age group over 35 years it reached 9%. After conducting the Spearman test in the Halsil test, the significant relationship between maternal age and the incidence of LBW was p (Sig) 0.02 (<0.05). Public health programs should focus more on education and intervention for pregnant women, especially those in their teens and the elderly. This is important to reduce the number of LBW and improve maternal and infant health. In the future, further research is needed to explore other factors that may affect LBW.